Justice Perception and Work Engagement among Teachers: Study of Govt. Business and Commerce Schools of Sindh - Chandio, Javed Ahmed; Anwer, Sadia; Ashraf , Muhammad; Shaikh , Saifullah (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study was to empirically investigate the impact of Justice Perception on Work Engagement. In order to substantiate the rationale of the study, the data was gathered making the permanent faculty members as respondents of the study engaged in various Business and Commerce Schools/Institutes of Sindh. Cross sectional survey based study has used an adopted data collection instrument to collect the data from 300 faculty, using Krejice and Morgan (1970) sample size for the study was determined. Probability sampling technique was used to target the accessible population. Applying the self determination theory (Deci & Ryan, 1985) and using deductive approach the formulated hypotheses were tested. Using multiple linear regression analytical technique the hypotheses were tested. The results revealed that Distributive Justice, and Interactional Justice and Significant and positive Impact on Employee Engagement. Whereas the Procedural Justice did not show any impact on work engagement. The outcome of the study significantly recommends that if the fairness in distribution, and treatment is uphold the employees dedication toward the job will be increased.